Adaptability and nutritional analysis of a newly isolated Chlorella sp. NeZha in brackish and marine environments with potential bioeconomic impacts - Yuan, Shuai; Du, Ming; Li, Xianhui; Xu, Ke; Zhang, Kaining; Liu, Xiaoya; Wang, Jiangxin (Frontiers in Nutrition, 2024)
Introduction The microalga Chlorella sp. NeZha, recently isolated from a balcony environment, shows significant adaptability across various salinity conditions, including seawater (SeaW), freshwater (FreshW), and high salinity levels (45‰). This study investigates its potential for sustainable aquaculture and biotechnological applications. Methods Morphological and genetic identification were conducted using optical microscopy and DNA sequencing. The microalga was cultivated in a 400 L outdoor photobioreactor, and its biochemical composition, including chlorophyll a, carbohydrate, protein, and lipid content, was analyzed. Its compatibility with zooplankton and growth in aquaculture wastewater were also evaluated. Results Chlorella sp. NeZha produced chlorophyll a at concentrations exceeding seaweed and Spirulina by 10- and 5-fold, respectively, with a dry weight chlorophyll a content of 34.25 mg/g and 25 pg./cell. The microalga also contained carbohydrate (~33%), protein (~20%), and lipids (~14%). It was compatible with zooplankton species, such as rotifers and brine shrimp, and showed promising growth in aquaculture wastewater. Discussion The findings suggest that Chlorella sp. NeZha is a viable candidate for sustainable aquaculture and biotechnological applications, offering high nutritional value and environmental resilience. Its adaptability to diverse salinity conditions and ability to thrive in wastewater highlight its potential for bioremediation and use as feedstock for zooplankton. Further research is recommended to optimize its cultivation and explore broader applications.